2014
DOI: 10.4103/0974-2077.138326
|View full text |Cite
|
Sign up to set email alerts
|

Fractional CO 2 laser resurfacing as monotherapy in the treatment of atrophic facial acne scars

Abstract: Background:While laser resurfacing remains the most effective treatment option for atrophic acne scars, the high incidence of post-treatment adverse effects limits its use. Fractional laser photothermolysis attempts to overcome these limitations of laser resurfacing by creating microscopic zones of injury to the dermis with skip areas in between.Aim:The aim of the present study is to assess the efficacy and safety of fractional CO2 laser resurfacing in atrophic facial acne scars.Materials and Methods:Sixty pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 29 publications
1
56
1
5
Order By: Relevance
“…In this work, the best improvement happened in rolling and ice pick scars and the least improvement was found in boxcar scars. In contrast, Majid et al found that rolling and superficial boxcar scars responded better than pitted scars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the best improvement happened in rolling and ice pick scars and the least improvement was found in boxcar scars. In contrast, Majid et al found that rolling and superficial boxcar scars responded better than pitted scars.…”
Section: Discussionmentioning
confidence: 99%
“…These microthermal treatment zones provide deep penetration and, subsequently, collagen remodeling and dermal regeneration can be achieved. Moreover, the tissue surrounding each column is spared, which leads to faster re‐epithelization and better wound healing than traditional CO 2 ablation . Platelet‐rich plasma (PRP) therapy is an autologous preparation of platelets in concentrated plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Atrophic scars can result from any inflammatory skin disease, causing sufficient damage to the epidermis and dermal collagen. 6 One of the most common causes of atrophic scars on the face is severe nodular or nodulocystic acne. 6 Atrophic acne scars are divided into four main morphological types: ice pick/pitted, boxcar, rolling, and linear.…”
Section: Acne Scarsmentioning
confidence: 99%
“…6 One of the most common causes of atrophic scars on the face is severe nodular or nodulocystic acne. 6 Atrophic acne scars are divided into four main morphological types: ice pick/pitted, boxcar, rolling, and linear. 6 Facial resurfacing with fractional lasers is currently one of the most effective treatment options for acne scars.…”
Section: Acne Scarsmentioning
confidence: 99%
See 1 more Smart Citation